Collective and decentralized management model in public hospitals: perspective of the nursing team (Revista Latino-Americana de Enfermagem, 2011)
This research aims to present the implementation of the collective and decentralized management model in functional units of a public hospital in the city of Ribeirão Preto, state of São Paulo, according to the view of the nursing staff and the health technical assistant. This historical and organizational case study used qualitative thematic content analysis proposed by Bardin for data analysis. The institution started the decentralization of its administrative structure in 1999, through collective management, which permitted several internal improvements, with positive repercussion for the care delivered to users. The top-down implementation of the process seems to have jeopardized workers adherence, although collective management has intensified communication and the sharing of power and decision. The study shows that there is still much work to be done to concretize this innovative management proposal, despite the advances regarding the quality of care.